2016
DOI: 10.3389/fpls.2015.01152
|View full text |Cite
|
Sign up to set email alerts
|

Application of Infrared and Raman Spectroscopy for the Identification of Disease Resistant Trees

Abstract: New approaches for identifying disease resistant trees are needed as the incidence of diseases caused by non-native and invasive pathogens increases. These approaches must be rapid, reliable, cost-effective, and should have the potential to be adapted for high-throughput screening or phenotyping. Within the context of trees and tree diseases, we summarize vibrational spectroscopic and chemometric methods that have been used to distinguish between groups of trees which vary in disease susceptibility or other im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
(99 reference statements)
1
32
0
Order By: Relevance
“…4), we inferred that this is likely also associated with ethylene emission induced by GPD treatment36. Similar results were also obtained in Populus and oil palm, which showed that PtIDA and PtIDL1 were expressed more highly in leaves after shade treatment (a similar treatment to GPD resulting in carbohydrate stress), and EgIDA2 and EgIDA5 could be induced by ethylene23, further supporting that IDA functions in the ethylene-response pathway.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…4), we inferred that this is likely also associated with ethylene emission induced by GPD treatment36. Similar results were also obtained in Populus and oil palm, which showed that PtIDA and PtIDL1 were expressed more highly in leaves after shade treatment (a similar treatment to GPD resulting in carbohydrate stress), and EgIDA2 and EgIDA5 could be induced by ethylene23, further supporting that IDA functions in the ethylene-response pathway.…”
Section: Discussionsupporting
confidence: 82%
“…Briefly, IDA encodes a peptide ligand that forms a complex with redundant receptor-like kinases HAE and HSL2, which presumably activates a MITOGEN-ACTIVATED PROTEIN KINASE (MAPK) cascade that acts to regulate downstream KNOX-like transcription factor BP/KNAT1. Recently, it has been proposed that the involvement of this signaling module in abscission processes is conserved in other plant species2223. However, so far, the characterization of key regulators in control of abscission has been reported mainly in the model plants tomato and Arabidopsis ; these factors are largely unknown in perennial woody plants, especially in important horticultural cultivated fruit crops, such as litchi.…”
mentioning
confidence: 99%
“…Zhang Keqin's research further indicated the specific locations of Raman characteristic peak position and demonstrated the group vibration form of sugars, proteins, and carbohydrates in cereals . Raman spectroscopy can also be used directly in plants to determine the bacterial and viral diseases …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quality of agricultural and forestry products has been assessed by FTIR (Bureau et al, 2019). FTIR has also been used for the detection of plant pathogens such as Fusarium in maize (Kos et al, 2002), huanglongbing disease in citrus (Hawkins et al, 2010), Geosmithia-Ophistoma complex in trees (Conrad and Bonello, 2016), and different leaf viruses in grapevines (Topală et al, 2017).…”
mentioning
confidence: 99%